The complement system and toll-like receptors as integrated players in the pathophysiology of atherosclerosis. Issue 2 (August 2015) - Hovland, Anders; Jonasson, Lena; Garred, Peter; Yndestad, Arne; Aukrust, Pål; Lappegård, Knut T.; Espevik, Terje; Mollnes, Tom E.
Abstract: Despite recent medical advances, atherosclerosis is a global burden accounting for numerous deaths and hospital admissions. Immune-mediated inflammation is a major component of the atherosclerotic process, but earlier research focus on adaptive immunity has gradually switched towards the role of innate immunity. The complement system and toll-like receptors (TLRs), and the crosstalk between them, may be of particular interest both with respect to pathogenesis and as therapeutic targets in atherosclerosis. Animal studies indicate that inhibition of C3a and C5a reduces atherosclerosis. In humans modified LDL-cholesterol activate complement and TLRs leading to downstream inflammation, and histopathological studies indicate that the innate immune system is present in atherosclerotic lesions. Moreover, clinical studies have demonstrated that both complement and TLRs are upregulated in atherosclerotic diseases, although interventional trials have this far been disappointing. However, based on recent research showing an intimate interplay between complement and TLRs we propose a model in which combined inhibition of both complement and TLRs may represent a potent anti-inflammatory therapeutic approach to reduce atherosclerosis. Highlights: Innate immunity is an important player in the inflammatory process underlying atherosclerosis. The complement system and the Toll-like receptor family are two main branches of innate immunity. Complement and Toll-like receptors are upregulated in atherosclerosis. The two systems cross-talk intensively and are possible targets for treatment of atherosclerosis.